Filogeografia de Jupiaba acanthogaster (Characiformes, Characidae) das bacias dos rios Paraguai, Xingu e Tapajós - Jacob, Rodrigo Correa Migueis (2012)
The modern Paraguay river basin drains an area of about 1.1 million square kilometer in South America, with headwaters in Brazil, Bolivia, Paraguay and Argentina, flowing into the La Plata basin (Paraguay-Paraná). The Paraguay river basin extends over 6,600 km from north to south and 3,300 km from east to west. Along its north and northeastern borders, the Paraguay basin share headwater divides with the Tocantins, Xingu and Tapajós basins. Distributions of several freshwater fish species from the central Brazilian shield are not restricted to a single basin. Instead, these species occurs in more than one river basin, such as, Jupiaba acanthogaster, which presents a wide geographical distribution, occurring in several streams draining the Brazilian Central Plateau, including the Paraguay, Upper Tapajos, and Tocantins river basins. The historical aspects that led to the contemporary distribution of this species and consequently its genetic structure, can be identified by the phylogeography. Therefore, understanding these processes allow inferences on hierarchical models of genetic differentiation and phylogeographic structure, which reflect the geographical history of the studied taxa and region. The current geographical distribution of endemic groups in South America are presumably directly associated with such events and can be investigated based on the study of phylogenetic patterns among lineages and interpreted according to recent advances in the field of plate tectonics in South America throughout the Cenozoic. Phylogenetic studies using molecular markers have contributed to a better understanding of the hierarchical patterns of the fish fauna genealogy and distribution, and corroborate biogeographic hypotheses. It is expected that the use of molecular markers such as mitochondrial DNA (mt DNA) would tell the deepest levels of phylogenetic divergence by presenting a rapid evolutionary rates in animal populations and being transmitted mostly through maternal lineage, without recombination, consisting in a useful tool in phylogenetic studies at populations levels. In this study, 77 specimens of Jupiaba acanthogaster collected at 15 different locations in the Paraguay, Xingu and Tapajós basins were analyzed and sequenced using the enzymatic gene Cytochrome Oxidase subunit I of mt DNA. The relatively high genetic distances, large number of unique haplotypes, the formation of three sets in the haplotype network by many mutational steps, significant Fst values and setting values above eight-step mutations, indicate that the populations of Paraguay, Tapajos and Xingu are evolutionarily distinctly lineages without reproductive connectivity that can produce gene flow between them.